Editorial - Katherine Bullock (International Institute of Islamic Thought, 2006)
When the tribes of Makkah decided to rebuild the Ka`bah, they worked together well until it was time to return the Black Stone to its corner. Each clan wanted the honor of this task, and tensions ran high for four or five days due to the stalemate over who would have the honor of lifting the Black Stone so that it could be returned to its proper place. With battle preparations underway, one man decided to try and avert a fight by suggesting a rather unorthodox idea: The first man to walk into the area would be appointed to arbitrate the dispute. Everyone agreed and began to wait. And so it was that Muhammad ibn Abdullah was the first to enter. Seeing this, the men reached a spontaneous agreement that he was indeed the best one to resolve this crisis, for he was known to all of them as a person of truth. Muhammad analyzed the situation and then asked for a cloak. Telling them to spread it out on the ground, he asked each clan to take hold of a corner. After placing the Black Stone in the middle, he asked them to raise the cloak so that he could place the Black Stone back in its proper place. This was Muhammad ibn Abdullah, a man of truth, integrity, and peace; a man who, according to Muslim belief, later became the last Prophet of God. Muhammad ibn Abdullah: about whom Muslims say “salla Allahu `alayhi wasallam” (May the peace and blessings of God be upon him) each time his name is mentioned; about whom they ask God to bless, just as He had blessed Abraham his family, at each of the five daily prayers; about whom it is said that God say ten prayers on anyone who says one prayer on him. In contrast with the 1,400 year old Muslim tradition of reverence toward Muhammad ibn Abdullah (pbuh), (indeed toward all of the prophets), a European tradition gradually sprung up dedicated to depicting Muhammad ibn Abdullah as an evil “magician” out to destroy Christendom. Pope Innocent III (1161-1216) even called him the Anti-Christ. During the medieval era, the bogey used to frighten naughty children into obedience was “Mahomet.” This negative image of Prophet Muhammad (pbuh) remains deeply ingrained in the European psyche (and, by extension, the colonized New World, now known as “the West”). Indeed, it is so deeply ingrained that ...